Functional near-infrared spectroscopy experiment to study functional plasticity in adult auditory cortex after cochlear implant switch-on - Fehner, Wiete (My University, 2021)
Although cochlear implants (CIs) have become a common treatment for sensorineural hearing loss (WHO, 2019), little is known on what happens in the brain after CI switch-on. The aim of this study is to develop a functional near-infrared spectroscopy (fNIRS) experiment to investigate plasticity in the auditory cortex (AC). The study is based on the results of previous fMRI studies in normal-hearing listeners (NHLs) showing that stimulus-dependent and attention effects are associated with distinct activation patterns in the human AC (Alho et al., 2014; Häkkinen et al., 2015; Rinne, 2010). I assume that these activation patterns can be measured with fNIRS and used as functional probes to investigate plastic changes in the human AC after CI switch-on. fNIRS is an advantageous technique for studies in cochlear implant listeners (CILs) as it does not interfere with the CI. Twelve NHLs participated in the study that was designed to test the following hypotheses: (1) stimulus-dependent effect in the human AC can be detected with fNIRS, (2) the intermodal attention effect in the human AC can be detected with fNIRS, (3) the contralateral attention effect in the human AC can be detected with fNIRS, and (4) fNIRS can be used to investigate the distribution of AC activation along the STG. The measurements were conducted using a newly installed Imagent v2 (ISS Inc., Champaign, IL, USA) system. Data were analyzed using repeated measures ANOVAs and paired sample t-tests. Contrary to the hypotheses, the results reveal no systematic AC activations in the fNIRS signal in the present experiment. Possible reasons for this are: (1) a small sample size, (2) physiological noise from extracerebral sources, (3) time-locked noise (breathing and movement), (4) non-optimal source-detector distances, (5) low number of repetitions per condition, and (6) non-optimal duration of resting periods. Subsequent studies should test the impact of these potential confounds so that stimulus-dependent and attention effects can be utilized to study AC plasticity in CILs with fNIRS.
Keywords: Cochlear implant listeners, Auditory cortex, Plasticity, fNIRS, Auditory attention effects, Auditory stimulus-dependent effects